MOU exchange ceremony between UiTM and Mayflax Sdn. Bhd / Nur Halina Mustafa, Zakiah Mohd Noordin and Gurmeet Kaur Surindar Singh - Mustafa, Nur Halina; Mohd Noordin, Zakiah; Singh, Gurmeet Kaur Surindar (Faculty of Pharmacy, 2024)
A Memorandum of Understanding (MoU) Ceremony Exchange between UiTM and Mayflax Sdn. Bhd. was formalised between Universiti Teknologi MARA (UiTM) and Mayflax Sdn. Bhd. to foster collaboration between academia and industry by sharing information and skills. The ceremony was held on May 8, 2024, at the Gallery, Faculty of Pharmacy, UiTM Selangor Branch, Puncak Alam Campus.